Lignin valorization for the production of renewable chemicals: State-of-the-art review and future prospects. (December 2018) - Cao, Leichang; Yu, Iris K.M.; Liu, Yaoyu; Ruan, Xiuxiu; Tsang, Daniel C.W.; Hunt, Andrew J.; Ok, Yong Sik; Song, Hocheol; Zhang, Shicheng
Graphical abstract: Highlights: Aromatics and carbon materials can be produced from lignin valorization. Heterogeneous or electrocatalytic hydrogenolysis is promising for aromatics production. Lignin biochar/hydrochar can serve as new carbon materials for emerging applications. Efficient lignin depolymerisation and degradation is the key to scaled-up valorization. Abstract: Lignin is an abundant biomass resource in aromatic structure with a low price in market, which can serve as renewable precursors of value-added products. However, valorization rate of annually produced lignin is less than 2%, suggesting the need for technological advancement to capitalize lignin as a versatile feedstock. In recent years, efficient utilization of lignin has attracted wide attention. This paper summarizes the research advances in the utilization of lignin resources (mainly in the last three years), with a particular emphasis on two major approaches of lignin utilization: catalytic degradation into aromatics and thermochemical treatment for carbon material production. Hydrogenolysis, direct pyrolysis, hydrothermal liquefaction, and hydrothermal carbonization of lignin are discussed in detail. Based on this critical review, future research directions and development prospects are proposed for sustainable and cost-effective lignin valorization.